Menggadaikan Kembali Tanah Gadai - Wahyudi, Wahyudi; Mariana Mariana (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2024)
This research discusses the practice of re-mortgaging pawned land according to Islamic law and positive law in Simpang Tiga District. This study is a type of qualitative research using field research and library research methods. The results of the research show that the practice of re-mortgaging land in Simpang Tiga District is common, especially when the land owner needs money urgently, but the land owner has not been able to pay off the loan, so the pawner pawns the land to another party without prior notification. first to the land owner because the agreement mechanism tends to be done verbally, which can cause risk and confusion. According to Islamic law, it is largely in accordance with the principles of Islamic law, especially because it is carried out on the basis of mutual assistance in society and in urgent situations. However, there are some issues to be aware of. One of them is re-mortgaging land without the land owner's permission, which may violate the principle of the validity of pawn transactions. The principles of Islamic law, such as agreements, rights and obligations, and collateral management, should be taken into account in implementing pawning practices. And positive law is permissible (legal), the pawn right can be transferred by the pledgor to another party with or without the land owner's consent, based on the regulations on the transfer of land use rights with reference to Article 37 paragraph (1) of Government Regulation no. 24 since 1997.